The effects of motor taxi operation on the profitability sustainability of tricycle operation the case of Mountain View First Street Tricycle Operators and Drivers' Association (MVFS-TODA). - Darang, John Patrick; Manalo, Franchesca Joy
This study examined the profitability and sustainability of tricycle operations among members of the Mountain View First Street Tricycle Operators and Drivers' Association (MVFS-TODA) following the rise of motor taxi services in Barangay Balibago, Angeles City, Pampanga. Specifically, it aimed to (1) determine whether there is a significant difference in the net income of MVFS-TODA members before and after the introduction of motor taxis and (2) assess the economic, social, and environmental sustainability of tricycle operations in light of this competition. The study applied the theory of the firm and the concepts of economic, social and environmental sustainability as its theoretical framework. Data were collected through face-to-face surveys and interviews with 40 respondents. Findings revealed a significant decline in the net income of MVFS-TODA members, with average daily earnings dropping from ₱1,150.00 to ₱537.50 (t-value=11.11, p-value= 0.000) after the introduction of motor taxis. This decline may suggest emerging job instability among tricycle drivers, possibly indicating concerns about social sustainability. While both modes contribute to air pollution, tricycles, particularly older units, appear to emit more pollutants, which may have implications for environmental sustainability. Based on reported trends, traditional tricycle operations seem to face increasing economic, socially and environmental pressures. Theoretical frameworks used in the study highlight possible livelihood and ecological challenges reported by drivers. To address these issues, the study recommends policy reforms such as fare regulation adjustments, optimized passenger capacity, financial assistance programs, and stricter environmental regulations.